NASA-ESA TRANS-ATLANTIC TRAINING (TAT) 2013-2015 - Štych, P.; Mouratidis, A.; Sarti, F.; Gutman, G. (Bulletin of the Geological Society of Greece, 2016)
Since 2013, NASA and ESA, in cooperation with Charles University in Prague (Czech Republic), have been joining forces and sharing expertise within the organization of annual Trans-Atlantic-Training (TAT) events in Eastern European countries. TAT concerns capacity building on Earth Observation from Space and focuses mainly on land cover/land use applications. With three TATs already organized between 2013 and 2015, the purpose of this paper is to provide an overview of the context and achievements so far, to increase the visibility of these events to larger audiences in Eastern Europe and to discuss the future prospects. To this end, some background information is initially provided, with subsequent description of each TAT event, concerning its organization, thematic content and participants. The paper concludes with an overall assessment and a vision for the future of TAT, including its enlargement with the engagement of participants from more countries.